2019
DOI: 10.1002/asjc.1990
|View full text |Cite
|
Sign up to set email alerts
|

Command filtered path tracking control of saturated ASVs based on time‐varying disturbance observer

Abstract: This paper investigates the path-tracking control problem for an autonomous surface vessel (ASV) with unknown time-varying disturbances and input saturation. A robust nonlinear control law is proposed based on a disturbance observer and an auxiliary system in the context of command filtered control.The disturbance observer is constructed to estimate the unknown time-varying disturbances, the auxiliary dynamic system is employed to handle input saturation, and the compensator based command filtered control tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
(107 reference statements)
0
14
0
Order By: Relevance
“…Theorem 1 For a group of autonomous underwater vehicles with kinematics and dynamics in (8) under dynamic control law (25) with update law (26), and kinematic control law (17) with command filter (5) and error compensator (18), the following results hold: 1). The formation tracking control can be achieved in a fixed time, denoted as T s .…”
Section: Formation Control With Velocity Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Theorem 1 For a group of autonomous underwater vehicles with kinematics and dynamics in (8) under dynamic control law (25) with update law (26), and kinematic control law (17) with command filter (5) and error compensator (18), the following results hold: 1). The formation tracking control can be achieved in a fixed time, denoted as T s .…”
Section: Formation Control With Velocity Measurementmentioning
confidence: 99%
“…From the above analysis, it can be concluded that the formation tracking system with velocity observerbased control law (46) does not escape in any finite time interval. Following the analysis at the beginning of the proof, one has that the closed-loop system under (17), (18), (42) and (46) is practically fixed-time stable. This completes the proof.…”
Section: Denote the Least Upper Bound Bymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the nonlinear backstepping control technique is proved with its effectiveness and designing simplicity to use for controlling the marine vessels. In [14] and [15], a disturbance observer is used to estimate unknown external disturbance, then combining backstepping method to accomplish trajectory tracking. Reference [16] combines adaptive feedback approximation technique and backstepping to design an adaptive neutral network control.…”
Section: Introductionmentioning
confidence: 99%
“…(2) The traditional backstepping approaches [14], [15] can only achieve the uniformly ultimately bounded convergence, i.e., the tracking error only converges to a region. However, the proposed finite-time backstepping controller can accomplish zero error tracking in finite time, which adopts a finite-time command filter based on the first-order Levant differentiator to obtain virtual control's derivative.…”
Section: Introductionmentioning
confidence: 99%